Modulating Electronic Structure of Metal‐Organic Framework for Efficient Electrocatalytic Oxygen Evolution - Xue, Ziqian; Li, Yinle; Zhang, Yawei; Geng, Wei; Jia, Baoming; Tang, Jia; Bao, Shixiong; Wang, Hai‐Ping; Fan, Yanan; Wei, Zhang‐wen; Zhang, Zishou; Ke, Zhuofeng; et al. (Advanced energy materials, 2018)
Exploring effective electrocatalysts for oxygen evolution reaction (OER) is a crucial requirement of many energy storage and conversion systems, involving fuel cells, water splitting, and metal–air batteries. Herein, a heterogeneity metal‐organic framework (MOF) is prepared by the assembling of metals, terephthalic (A) and 2‐aminoterephthalic ligands (B), defined as A2.7B‐MOF‐FeCo1.6. More importantly, A2.7B‐MOF‐FeCo1.6 exhibits excellent OER activity with an ultralow overpotential of 288 mV at 10 mA cm−2 and a Tafel slope of 39 mV dec−1. The high electrocatalytic performance for OER is attributed to the optimized electronic structure of the intrinsic catalytic center in MOFs via the engineering of the metal node and linkers. The work offers not only a benchmark for pure MOFs in electrocatalysis but also a new efficient strategy to improve electrocatalytic performance by electronic structure engineering of catalytic active centers in MOFs. A heterogeneity MOF A2.7B‐MOF‐FeCo1.6 is prepared by structurally tailoring metal nodes and organic linkers. It can serve as an efficient electrocatalyst with superior oxygen evolution reaction activity owing to modulations in the electronic structure of the catalytic center.